(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
A new online social network service – Threads – was recently created and launched by Mark Zuckerberg to compete with Twitter. The rate at which people throughout the world accepted and created accounts on this new social network within hours of its creation and launching was prodigious. Conflicts have been inevitable in the world. As one of the Sustainable Development Goals of the United Nations (SDGs) (Goal 16) has to do with peaceful coexistence by the year 2030, this paper aims at comparing the features of Twitter that can be used for conflict resolution to the emerging features of Threads. The paper gives the origin and acceptance of Threads. The discussion in the paper is based on the review of some selected literature, Public Sphere as a Theory of social media, an empirical review of a previous study, and comparisons of some features of Twitter with those of Threads. The paper concluded by giving a recommendation that while Twitter as a social network should not be jettisoned especially in resolving conflicts, the new social network – Threads – should be studied more to discover how it can be used better to resolve conflicts and promote peaceful coexistence in society thereby achieving Goal 16 of the SDGs by the year 2030.